HLA-DR and DQ Antigens in Iraqi Patients with Behget's Disease - AL-Joofy, Ikbal Kh.; AL-Muslih, raad; Al- Mousawy, khalida; AL-Waiz, mokaram M.; omer, amera Jaber (Journal of the Faculty of Medicine Baghdad, 2005)
Background: